Strabismus and Pediatric Psychiatric Illness: A Literature Review - Tiffany L. Huang; Stacy L. Pineles (MDPI AG, 2023)
Purpose: This literature review aims to investigate the potential association between strabismus and mental illness among children. Materials: The search was conducted in the PubMed and Google Scholar databases using a wide range of search terms related to strabismus, mental disorders, psychiatric illness, childhood, and adolescence. Results: Eleven published studies were included in this review. The findings from this review suggest an association between strabismus and mental illness. Negative attitudes and social bias against children with strabismus were also noted. Conclusions: These findings should alert healthcare providers to counsel children and their caregivers regarding the risk for mood disorders in children with strabismus and to consider mental health screening and referral as needed.